Consumer Preferences on the Selection of Minibus Rental Services - Bramantyo, Galih Aryo (Universitas Ciputra Surabaya, 2022)
The purpose of this study is to analyze and evaluate consumer preferences in choosing minibus rental services in Surabaya. The research method/approach used in this research is descriptive quantitative. The data analysis technique used in this research is conjoint analysis. Conjoint analysis is a technique that is specifically used to understand how consumers want or preferences for a product or service by measuring the level of usefulness and the relative importance of various attributes of a product. JN Transport management can determine market/customer penetration so that JN Transport can outperform competitors. In addition to market penetration, this research can be one of the management considerations to raise the brand (brand) that has been built by management. The management of JN Transport must also be able to see opportunities by analyzing the customers/clients that will be explored for cooperation. Determining the customer/client will be very influential in the future for the sustainability of JN Transport's business. Based on data analysis and discussion, the researcher can conclude that the combination is the most preferred and becomes the customer's attention when choosing to use the services of JN transport with the 5th combination where Hiace is the preferred fleet with driverless services and a 3-month contract method.